Wedding Invitation Cards from a Sociolinguistic Perspective: A Case Study from Jordan - Nathir Ghafar, Zanyar; Omar (Mohammad-Ameen) HAZAYMEH; Adam AL-JAWARNEH; Mufleh JARRAH (RADINKA JAYA UTAMA PUBLISHER, 2024)
This study explores wedding invitation cards from a sociolinguistic perspective, focusing on a case study from Jordan. The study highlights the cultural and communicative significance of wedding invitations in Jordanian society. The objective is to analyze the linguistic features, social functions, cultural values reflected in these invitations, and structure (the components) of the wedding cards. Methods include qualitative content analysis of a sample of wedding invitation cards collected from various regions in Jordan, supplemented by interviews with card designers and recipients. Results indicate that the language of the invitations is a blend of formal Arabic, colloquial expressions, and occasional English phrases, reflecting social hierarchies, regional identities, and influences from globalization. The study also reveals that wedding invitations serve as a medium for displaying social status, familial bonds, and cultural traditions. The study concludes that wedding invitation cards in Jordan are not merely functional artifacts but are rich in sociolinguistic meaning, providing insights into the interplay between language, culture, and society in contemporary Jordan.